Legal Review Of The Criminal Act Of Fraud Study Of Decision No. 1188/PID.B/2022/PN MDN - Batubara, Muhammad Miftahur Rizki; Fikri, Rahul Ardian; Ismaidar, Ismaidar (Fakultas Hukum Dehasen, 2025)
This study focuses on criminal law policies in dealing with fraud. Fraud is one of the crimes that often occur in society and is regulated in Article 378 of the Criminal Code (KUHP). This study aims to analyze the crime of fraud based on Decision No. 1188/Pid.B/2022/PN MDN. This study uses a normative legal method with a case study approach to examine how the court applies the elements of the crime of fraud in the case. The results of the study show that the court has decided this case by considering the elements of the crime of fraud as regulated in the Criminal Code. However, further analysis reveals several challenges in the application of the principle of justice, especially related to consideration of the victim's losses and the social impacts caused. This study recommends the need for improvements in aspects of law enforcement, including providing compensation to victims as a form of restorative justice.